MEASURING FOREIGN LANGUAGE ANXIETY : CONCERNING STUDENTS' MOTIVATION AND THEIR SELF-PERCEPTION - Mowafg Masuwd; Ermy Dikta Sumanik; Suhana Sarkawi; Mohammad Ahmad Bani Amer (International Journal of Teaching and Learning, 2024)
Student motivation refers to the internal or external drive that influences students' desire and effort in achieving learning goals, which can be intrinsic (drive from within) or extrinsic (drive from external factors such as rewards or praise). Self-perception is a student's view or belief of their ability and competence in a particular area or task. Both play an important role in the learning process, where high motivation and positive self-perception can increase engagement, performance and feelings of effectiveness in facing educational challenges. The review conducted in this study used the literature research method. The results of this study confirm the importance of supporting positive self-perception and increasing intrinsic motivation to reduce foreign language anxiety among students. Educators are advised to create a supportive learning environment and provide constructive feedback, as well as design learning activities that foster students' sense of success and self-confidence. Thus, students can better enjoy the foreign language learning process without the burden of excessive anxiety, and ultimately, improve their overall learning outcomes.